Relationship Between Self Efficacy And Coping Strategies With Anxiety In Women Victims Of Dating Violence - Heni Silva Runaweri; Christin Wibhowo (UNIVERSITAS PAKUAN, 2024)
Anxiety is an unpleasant subjective experience of worry or tension in the form of feelings of worry, tension and emotions experienced by a person. Anxiety is a certain symptom, namely facing an uncertain situation and uncertainty regarding one's ability to deal with the situation, in the form of unpleasant emotions experienced by the individual. The type of research used is quantitative using design cross sectional. The research will be carried out at Rifka Annisa Women’s Crisis Center. The population of this study were all clients who were victims of dating violence who complained to Women Crisis Center Rifka Annisa. The sample taken was 50 respondents who were selected using Purposive sampling. This research can be concluded that there is a relationship between Self-Efficacy and coping strategies and Anxiety in Women Victims of Dating Violence.